Pedagogical implications of conversational implicatures in Austen’s pride and prejudice - Talib Salman, Hawraa; Yusoff, Zailin Shah (Science & Engineering Research Support Society (SERSC), 2020)
This research was aimed at figuring out the meanings, their various forms, their intended sense used in pride and prejudice by Jane Austen. The data were collected through certain procedures focused on the theory of relevance. The utterances in dialogs which contain implications were selected and determined to be analyzed. Certain procedures were presented and defined used to analyze the data based on ‘Relevance theory’; which involves not only encoding and decoding messages through communication but also various other elements, comprising inference and context. Analyses and findings of the study reveal that there were 60 implications were distributed into strong and weak forms. As a follow-up, the study was performed to the second-semester students of the Baghdad University Graduate Program, resulting in no substantial correlation between the awareness of implications and significance theory of the respondents and their success in evaluating implications using the p-value hypothesis of 0.406 (p-value > 0.05).